FORMATION OF PROGRAM RESULTS OF TRAINING IN THE PROCESS OF STUDYING SOCIAL-POLITICAL DISCIPLINES - Bakumenko, O (Problems of Engineer-Pedagogical Education, 2019)
The article analyses the specifics of the formation of learning outcomes in the process of studying syllabic-political disciplines in higher educational institutions where disciplines of socio-political orientation are not profileal. The urgency of study of social and political disciplines in the conditions of modernization of the modern system of education and internal and external challenges facing the Ukrainian society to date is substantiated. Based on the approved standards of higher education for the first educational level, "bachelor", it is determined which of the general competences may be most fully formed during the study of socio-political disciplines, and what the results of training should be formed. It is substantiated which of the general competencies and related programmatic learning outcomes is the product of studying primarily socio-political disciplines, are civic in their content, and which are general scientific and are formed by all disciplines (including social ones) that are studied in higher educational institutions. A detailed review of the set of tools through which the study of discipline achieved the formation of specific program results. Particular attention is paid to those thematic elements of the course, which to the greatest extent can affect those and other skills and competences that become the content of certain learning outcomes. It has been established that in accordance with the approved standards of higher education, the main general competence of comprehension which is carried out during the study of socio-political disciplines is the formation of a conscious citizen, the member of the civil society, ho fully possesses knowledge of his rights and duties as a member of society, is well aware of the values of civil society and modern democracy, the rule of law, human and civil rights and freedoms in Ukraine, and as a result, on the basis of this knowledge, is able to form his own socially -conscious behavior, be prepared to use their rights and carry out duties, taking into account the norms of modern pluralistic democracy, the requirements of tolerance and respect for the rights of other participants in the sociopolitical process.